Biological Warfare against Agricultural Crops: Historical Aspects and Conventional Control - M. V. Supotnitskiy (Вестник войск РХБ защиты)
Highlights- means and methods of biological war against agricultural crops have been devised and tested at field test site andapproved during the Korean war;- this is a low-tech, but dangerous war, means of which don't have reliable conventional control.Relevance. The number of people who have fallen victims to famine is comparable to that the number of people who have suffered from nuclear weapons use. However, the means and methods of biological war against agricultural crops almost haven’t been dwelled upon in Russian scientific publications. This dulls our sense of danger and makes us inferior to foreign experts in this field.Purpose of the study is to consider the historical aspects of means of biological war against agricultural crops and conventional control tools that exist nowadays.Study base sources. The author has studied the Khabarovsk trials dedicated to crimes committed by Japanese military men; Report of the International Scientific Commission for the investigation of the facts concerning bacterial warfare in Korea and China (1952); official declassified documents on the United States biological weapons program, books and articles retrieved from full-text English scientific journals available on the Internet.Materials and methods. Analytical. The author used suggestions of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA).Discussion. The USA, Germany and Japan have been leaders in the development of biological weapons of this type since 1940–1950. Means and methods of war against agricultural crops are still powerful. This paper has thoroughly dwelled on this topic. Current trends have turned the situation in this field into chaos, the range of pathogens and their potential targets is constantly widening, there are no reliable conventional control tools.Conclusions. As we actually don’t fully understand the ways and methods of war against agricultural crops, we can miss the very onset of such a war and we won’t be able to detect the enemy. That is why we should broaden our knowledge in the field; this topic should be studied at the universities. Monocropping countries with poor farming techniques that grow mostly one-year-old plants are more vulnerable to biological weapons damage effects.